Rotenone: from modelling to implication in Parkinson’s disease - Radad, Khaled; Al-Shraim, Mubarak; Al-Emam, Ahmed; Wang, Feixue; Kranner, Barbara; Rausch, Wolf-Dieter; Moldzio, Rudolf (Folia Neuropathologica, 2019)
Rotenone ([2R-(2α,6aα,12aα)]-1,2,12,12a-tetrahydro-8,9-dimethoxy-2-(1-methylethenyl)-[1]benzopyran[3,4-b]furo [2,3-h][1]benzopyran-6(6aH)-one) is a naturally occurring compound derived from the roots and stems of Derris, Tephrosia, Lonchocarpus and Mundulea plant species. Since its discovery at the end of the 19th century, rotenone has been widely used as a pesticide for controlling insects, ticks and lice, and as a piscicide for management of nuisance fish in lakes and reservoirs. In 2000, Betarbet et al. reproduced most of the behavioural, biochemical and pathological features of Parkinson’s disease (PD) in rotenone-treated rats. Since that time, rotenone has received much attention as it would be one of the environmental neurotoxins implicated in etiopathogenesis of PD. Moreover, it represents a common experimental model to investigate the underlying mechanisms leading to PD and evaluate the new potential therapies for the disease. In the current general review, we aimed to address recent advances in the hazards of the environmental applications of rotenone and discuss the updates on the rotenone model of PD and whether it is implicated in the etiopathogenesis of the disease.